Biomarkers and Cellular Infiltration of the Bladder in Interstitial Cystitis/Bladder Pain Syndrome - Rashad Farkhad ogly Sholan (Journal of Urological Surgery, 2020)

(untitled)
Objective:To study the content of nerve growth factor (NGF), interleukin (IL)-8 in the urine, mast cells, and white blood cells in a biopsy of the bladder and the relationship between them in women with interstitial cystitis/bladder syndrome (IC/BPS).Materials and Methods:Forty-one women with IC/BPS (mean age: 46.6±14.0 years) and 20 women without IC/BPS (mean age: 35.3±9.7 years) were examined in this study. Cystoscopy with hydrodistension was performed. NGF and IL-8 were determined in the urine by enzyme-linked immunosorbent assay. The number of mast cells and leukocytes was determined in biopsy specimens of the bladder wall. Statistical calculations were performed in Excel 2016 (SPSS 15.0). Results were processed using the Pearson’s correlation coefficient to describe the relationships between variables.Results:Diffuse submucosal hemorrhages (43.9%) were more common. The level of NGF was 142.26±134.906 ng/mL, IL-8 was 51.3±9.36 pg/mL, and lymphocytes (238.0±166.42) and mast cells (82.27±38.76) predominated in the biopsy specimens. A correlation of the mast cells with the plasma cells (r=-0.228), neutrophils (r=-0.227), and lymphocytes (r=-0.156) was observed. NGF and IL-8 correlated with mast cells, neutrophils, and plasma cells with weak multidirectional bonds.Conclusion:With IC/BPS, the concentration of NGF and IL-8 in the urine is increased. In biopsy specimens, mainly lymphocytes and mast cells, the correlation of NGF and IL-8 with mast cells, neutrophils, and plasma cells is weak. These indicators can be included in a complex of diagnostic studies.